Retinal Nerve Fiber Layer Thickness Post-Laser Treatment in Diabetic Retinopathy: Argon versus Pattern Scanning Laser - Maimunah Binti Abdul Muna'aim; Ropilah AR; Othmaliza O; Mushawiahti M (Universiti Kebangsaan Malaysia, 2024)
Non-Indexed Publication